Early Childhood, Aging, and the Life Cycle Mapping Common Ground - Silin, Jonathan G. (Critical Cultural Studies of Childhood, 2018)
In this book, Silin maps the common ground between early childhood and the period sociologists call "young-old age." Emphasizing the continuities that bind children and adults rather than the differences that traditional developmental psychology claims separate us, he focuses on the themes we all manage across a lifetime. Building on memoir and narrative, Silin argues that when we recognize how the concerns of childhood continue to thread their way through our experience, we look anew at the shape of our lives. This book highlights the powerful generative acts through which people of all ages find new meanings and relationships to compensate for the individual and social losses that mark our lives. .